Virtual Reality and Cultural Preservation: Innovating the Past, Protecting the Future - Theoulaki Μaria Zoi (HAPSc Policy Briefs Series, 2024)
In an age where technological advancements shape every facet of our lives, virtual reality (VR) stands at the forefront of innovation, offering transformative possibilities across various sectors. One particularly exciting application of VR is in the realm of cultural preservation. By enabling immersive experiences and detailed digital documentation, VR presents a powerful tool for protecting and revitalizing cultural heritage. However, this innovation comes with its own set of challenges and responsibilities, particularly in the context of international relations and legal frameworks. This article explores how VR is reshaping cultural preservation, balancing the fine line between innovation and safeguarding the past, and the necessary international legal measures to support this balance.